Awareness assessment of Safe-Guard® in the U.S. cattle industry - Ligtenberg, Tiffany G. (Kansas State University, 2017)
This research focuses on the cattle producer’s overall awareness of an internal deworming product available in the U.S. cattle market. Parasitism in cattle can be very costly for the producer, and identifying a need for deworming is instrumental to the decision-making process for animal health protocols. The additional cost of deworming products can be beneficial for profitability for cattle producers when used properly. Likewise, when there is no proven need for deworming products in certain operations, the additional cost is an unnecessary expense that can be avoided. Proper awareness and education regarding deworming products and the benefits they can provide is one crucial piece to improving herd health, better rates of gain, and increased profitability. The main objective of this study is to determine the awareness of non-handling formulations of Safe-Guard. To understand and assess awareness, a survey was used. A population of participants was developed and asked to participate in the survey either online or in hard copy. A binary logit is used to analyze how cattle producers make decisions in adopting animal health products into their operations. Influencing factors of operation type, size, location, producer’s age, and information sources are used in the assessment. Factors that were the most influential to the decision-making processes for producers were discussions with veterinarians, nutritionists, and animal health sales representatives. In addition to face-to-face discussions with neighboring producers/friends, industry meetings, and reading industry journals and publications were also important. These producers were aware of a few formulations of Safe-Guard, and used them within the previous twelve months of taking the survey. However, participants were generally unaware of the product, and its different formulations. Upon review of the assessed unawareness of the product formulations, it is apparent that the company needs to identify and select a better way to make producers aware. Different approaches to targeted marketing campaigns and more in depth product training for the animal health company’s sales representatives should be implemented to increase awareness and sales.
Keywords: Brand awareness; Logit; Safe-Guard; Animal health